An electrolyte and its application

By using electrolytes containing silanes, isocyanate compounds and fluorovinyl carbonate in lithium-ion batteries, the problem of interface damage caused by expansion of silicon negative electrode materials is solved, and gas production of the electrolyte is prevented at high temperatures, which significantly improves the high-temperature and electrochemical properties of the battery.

CN117219861BActive Publication Date: 2025-03-04GUANGZHOU TINCI MATERIALS TECH +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311290563.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-08
Publication Date
2025-03-04
Estimated Expiration
2043-10-08

AI Technical Summary

Technical Problem

The volume expansion of the silicon negative electrode material in lithium-ion batteries during circulation causes damage to the interface between the negative electrode sheet and the electrolyte, which deteriorates the battery performance. The existing electrolyte is prone to gas production at high temperatures, causing the battery to fail.

Method used

An electrolyte is adopted, which includes silanes, isocyanates and fluorovinyl carbonate. These components are used to construct a stable interface film on the surface of the negative electrode to inhibit the expansion of the silicon negative electrode material and prevent gas production of the electrolyte at high temperatures.

Benefits of technology

During long-term storage, the electrolyte is not easy to generate acidic substances, forming a high-quality SEI film, reducing the battery impedance, and improving the battery's high-temperature circulation and high-temperature storage performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004481255570000021
    Figure BDA0004481255570000021
  • Figure BDA0004481255570000031
    Figure BDA0004481255570000031
  • Figure BDA0004481255570000041
    Figure BDA0004481255570000041
Patent Text Reader

Abstract

The present invention provides an electrolyte and its application, the electrolyte includes silane of formula 1, isocyanate compounds and fluoroethylene carbonate; in formula 1, R1, R2, R3, R4 are each independently selected from hydrogen, halogen, substituted or unsubstituted C1-C30 alkyl, substituted or unsubstituted C2-C30 alkenyl, substituted or unsubstituted C2-C30 alkynyl, substituted or unsubstituted C1-C30 alkoxy, substituted or unsubstituted C1-C60 aryl, at least one of isocyanate group; and at least one of R1, R2, R3, R4 includes an unsaturated group. The electrolyte is not easy to generate acidic substances during long-term storage. The electrolyte is used in a battery, which helps to form a high-quality SEI film on the surface of the negative electrode, and effectively suppresses the high-temperature gas generation problem of silicon-based batteries, thereby reducing the battery impedance and improving the high-temperature cycle and high-temperature storage performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an electrolyte and application thereof, belonging to the technical field of energy. Background Art

[0002] With the advancement of science and technology and the diversification of energy demand, traditional energy is being consumed at an accelerated rate, and countries are accelerating their strategic deployment of new energy technologies. Among them, power batteries are rising with the development of new energy vehicles, and energy storage batteries are also booming with the development of clean energy. Since 2017, the competition in the new energy vehicle industry has become increasingly fierce. Power battery companies have continuously developed and updated their products in order to find a chemical power system that is more adaptable to the market, to meet users' requirements for high specific energy and endurance, and to be able to fully replace traditional energy passenger cars and buses.

[0003] Lithium-ion batteries are one of the important products in new energy technology. Traditional lithium-ion batteries use graphite to prepare negative electrodes, and the specific capacity of graphite is 372mAh g -1 , it is difficult to meet the higher specific energy requirements of lithium-ion batteries. Therefore, researchers at home and abroad have gradually turned their attention to silicon negative electrode materials with high specific capacity. However, although silicon negative electrode materials can improve the energy density of batteries to a certain extent, they are prone to huge volume expansion during the battery cycle, which will cause the interface film between the negative electrode sheet and the electrolyte to be continuously destroyed, causing the electrolyte to continue to decompose, and ultimately deteriorating the performance of the battery.

[0004] In order to solve the problem of battery performance deterioration caused by damage to the interface film between the negative electrode sheet and the electrolyte during the cycle of batteries containing silicon negative electrode materials, researchers proposed that a new electrolyte additive can be developed to build a stable interface film on the surface of the negative electrode sheet to reduce the negative effects caused by the expansion of silicon negative electrode materials. For example, fluoroethylene carbonate (FEC) is used as an electrolyte additive and added to the electrolyte to form a stable interface film on the surface of the negative electrode sheet, thereby effectively reducing the capacity loss caused by the silicon negative electrode material and reducing the interface impedance between the negative electrode sheet and the electrolyte. However, FEC will produce gas at high temperatures, causing battery failure or even explosion.

[0005] The prior art prepares an electrolyte by compounding tri(trimethylsilyl)phosphate with FEC to overcome the defect of FEC producing gas at high temperature. However, the electrolyte including tri(trimethylsilyl)phosphate is prone to generate impurities such as phosphoric acid during long-term storage of the battery, resulting in an increase in the acidity of the electrolyte. In addition, impurities such as phosphoric acid will react with other components in the electrolyte or with the electrode, thereby deteriorating the electrochemical performance of the battery. Summary of the invention

[0006] The present invention provides an electrolyte which is not easy to generate acidic substances during long-term storage. The electrolyte is used in a battery to help form a high-quality SEI film on the surface of the negative electrode and effectively inhibit the high-temperature gas generation problem of silicon-based batteries, thereby reducing battery impedance and improving the high-temperature cycle and high-temperature storage performance of the battery.

[0007] The invention also provides a battery containing the electrolyte, so the battery has relatively excellent electrochemical performance.

[0008] The present invention provides an electrolyte, which comprises silane shown in Formula 1, an isocyanate compound and fluoroethylene carbonate;

[0009]

[0010] Formula 1

[0011] In Formula 1, R1, R2, R3, and R4 are each independently selected from at least one of hydrogen, halogen, substituted or unsubstituted C1-C30 alkyl, substituted or unsubstituted C2-C30 alkenyl, substituted or unsubstituted C2-C30 alkynyl, substituted or unsubstituted C1-C30 alkoxy, substituted or unsubstituted C1-C60 aryl, and isocyanate;

[0012] At least one of R1, R2, R3, and R4 includes an unsaturated group.

[0013] The electrolyte as described above, wherein the substituents of R1, R2, R3, and R4 are each independently selected from a substituted or unsubstituted C1-C30 alkoxy group, a substituted or unsubstituted C2-C30 alkenyl group, a substituted or unsubstituted C2-C30 alkynyl group, and an isocyanate group.

[0014] The electrolyte as described above, wherein the silane includes a Si—O bond.

[0015] In the electrolyte as described above, the silane has a symmetrical structure.

[0016] The electrolyte as described above, wherein the silane is selected from the compounds shown in the following structure;

[0017]

[0018]

[0019] The electrolyte as described above, wherein the mass percentage of the silane is 0.5%-1% based on the total mass of the electrolyte.

[0020] The electrolyte as described above, wherein the mass percentage of the fluoroethylene carbonate is 5%-10% based on the total mass of the electrolyte.

[0021] In the electrolyte as described above, the mass percentage of the isocyanate compound is 0.1%-0.5% based on the total mass of the electrolyte.

[0022] The electrolyte as described above, wherein the electrolyte further comprises a lithium salt, and based on the total mass of the electrolyte, the mass percentage of the lithium salt is 12.5%-18%.

[0023] The present invention provides a battery, comprising the electrolyte as described above.

[0024] The electrolyte of the present invention has a simple composition and is not easy to generate acidic substances during long-term storage. The electrolyte is used in a battery, such as a secondary battery, which helps to form a more compact and stable SEI film on the negative electrode surface of the secondary battery, protects the electrode, and is conducive to improving the performance of the secondary battery.

[0025] Since the battery of the present invention includes the aforementioned electrolyte, the negative electrode surface has a dense and stable SEI film to further avoid contact damage between the electrode and the electrolyte. Therefore, the electrochemical device of the present invention has more excellent electrochemical properties, such as high-temperature cycling and high-temperature storage performance. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] A first aspect of the present invention provides an electrolyte comprising a silane represented by Formula 1, an isocyanate compound and fluoroethylene carbonate;

[0028]

[0029] Formula 1

[0030] In Formula 1, R1, R2, R3, and R4 are each independently selected from at least one of hydrogen, halogen, substituted or unsubstituted C1-C30 alkyl, substituted or unsubstituted C2-C30 alkenyl, substituted or unsubstituted C2-C30 alkynyl, substituted or unsubstituted C1-C30 alkoxy, substituted or unsubstituted C1-C60 aryl, and isocyanate;

[0031] At least one of R1, R2, R3, and R4 includes an unsaturated group.

[0032] Specifically in Formula 1, R1, R2, R3, and R4 are each independently selected from hydrogen, halogen (F, Cl, Br, I), substituted or unsubstituted C1-C30 alkyl (for example, cycloalkyl, branched alkyl, linear alkyl, substituted cycloalkyl, substituted branched alkyl, substituted linear alkyl), substituted or unsubstituted C2-C30 alkenyl (for example, linear alkenyl, branched alkenyl, cyclic alkenyl (cyclopentadienyl), substituted linear alkenyl, substituted branched alkenyl), At least one of a substituted or unsubstituted C2-C30 alkynyl group (for example, a straight-chain alkynyl group, a branched-chain alkynyl group, a substituted branched-chain alkynyl group, a substituted straight-chain alkynyl group, or a cyclic alkynyl group), a substituted or unsubstituted C1-C30 alkoxy group (for example, a straight-chain alkoxy group, a branched-chain alkoxy group, a substituted branched-chain alkoxy group, or a substituted straight-chain alkoxy group), a substituted or unsubstituted C1-C60 aryl group (for example, a phenyl group, a biphenyl group, a substituted phenyl group, or a substituted biphenyl group), and an isocyanate group.

[0033] The present invention does not particularly limit the substituents in R1, R2, R3, and R4, and may be substituents commonly used in the art, for example, may be at least one of halogen, ester, nitro, amino, cyano, substituted or unsubstituted alkyl, substituted or unsubstituted alkenyl, substituted or unsubstituted alkynyl, substituted or unsubstituted alkoxy, cyano, isocyano, isocyanate, and substituted or unsubstituted aryl.

[0034] And at least one of R1, R2, R3, and R4 includes an unsaturated group, for example, at least one of R1, R2, R3, and R4 can be selected from a substituted or unsubstituted unsaturated group (substituted or unsubstituted alkenyl, substituted or unsubstituted alkynyl, isocyano, isocyanate, and cyano), or the substituent of at least one of R1, R2, R3, and R4 is selected from an unsaturated group (substituted or unsubstituted alkenyl, substituted or unsubstituted alkynyl, isocyano, isocyanate, and cyano).

[0035] The electrolyte of the present invention comprises silane shown in Formula 1, fluoroethylene carbonate (FEC) and isocyanate compounds. The silane shown in Formula 1, fluoroethylene carbonate and isocyanate compounds can act synergistically to improve the comprehensive performance of the battery. Specifically, on the one hand, the silane shown in Formula 1 is not easy to produce acidic substances during the long-term storage of the electrolyte, which is beneficial to prolong the service life of the battery and improve the electrochemical performance of the battery; and the silane shown in Formula 1 can also eliminate HF acid in the electrolyte, avoid HF acid corrosion of the electrode material, and improve the electrochemical performance of the battery; on the other hand, the silane shown in Formula 1 includes unsaturated groups, and during the charge and discharge process of the battery, the unsaturated groups are very easy to polymerize or cross-link to form a film, which can assist FEC in building a stable interface film and improve the electrochemical performance of the battery (for example, room temperature cycle performance and high temperature cycle performance); at the same time, the isocyanate compound can eliminate the side reactions generated by the silane in the system, avoid the generation of trimethylsilyl fluoride (TMSF), and enhance the ability of the silane to inhibit high-temperature gas production. In addition, during the charge and discharge process of the battery, the isocyanate compound will generate polyurethane, which not only has excellent elasticity, but also has outstanding thermal insulation performance, and can effectively inhibit the expansion of the silicon material in the negative electrode sheet and the intrusion of the generated interface film by the external high temperature, thereby improving the high temperature storage performance and high temperature cycle performance of the battery.

[0036] It is worth mentioning that when silane contains Si-O bonds, the Si-O bonds have higher bond energy, which not only helps to further improve the high temperature resistance of the electrolyte, but also can form a more high temperature resistant SEI film during the charge and discharge process of the battery, further improving the high temperature performance of the battery;

[0037] When silane has a symmetrical structure (axially symmetrical structure or centrally symmetrical structure), it can not only reduce the preparation cost of silane and promote the large-scale application of silane, but also the silane molecules with symmetrical structure have low activity, convenient storage, and are not prone to side reactions during storage, which helps to improve the electrochemical performance of the battery.

[0038] In some embodiments of the present invention, when the substituents of R1, R2, R3, and R4 are each independently selected from a substituted or unsubstituted C1-C30 alkoxy group, a substituted or unsubstituted C2-C30 alkenyl group, a substituted or unsubstituted C2-C30 alkynyl group, or an isocyanate group, the electrochemical performance of the battery can be further improved.

[0039] Exemplarily, the silane may be selected from the compounds shown in the following structures;

[0040]

[0041]

[0042] It is understood that in the present invention, the above silane can be obtained by commercial purchase or by self-preparation in the laboratory using a method commonly used in the art. And the compound shown in the above structural formula is only given as an example, which can be a cis structure or a trans structure.

[0043] The present invention does not particularly limit the isocyanate compound, and can be an isocyanate compound commonly used in the art. For example, the isocyanate compound can be selected from at least one of hexamethyl diisocyanate (B1), p-phenylene diisocyanate (B2), triisocyanate-methyl-silane, 1,4-diisocyanate-2-toluene (B3), γ-isocyanate propyl trimethoxy silane (B4), γ-isocyanate propyl triethoxy silane, γ-isocyanate propyl methyl dimethoxy silane, isocyanate propyl methyl diethoxy silane, γ-isocyanate propyl dimethyl methoxy silane, α-isocyanate methyl trimethoxy silane, α-isocyanate methyl triethoxy silane and α-isocyanate methyl dimethoxy silane.

[0044] Furthermore, when the isocyanate compound is selected from at least one of hexamethyl diisocyanate, p-phenylene diisocyanate and 1,4-diisocyanate-2-toluene, the isocyanate compound cooperates with FEC and silane to further improve the electrochemical performance of the battery. In particular, when the silane contains an isocyanate group, the isocyanate compound can be selected from at least one of hexamethyl diisocyanate, p-phenylene diisocyanate and 1,4-diisocyanate-2-toluene.

[0045] The inventors found in their research that, on the one hand, when silane contains carbon-carbon unsaturated bonds (double bonds or triple bonds), the presence of carbon-carbon unsaturated bonds can cause silane to self-polymerize, and the Si-O component in silane can make the interface film generated by silane polymerization more resistant to high temperatures, making up for the serious side reaction defect of FEC at high temperatures; on the other hand, active silane can eliminate HF in the electrolyte and reduce the impact of HF. The addition of isocyanate compounds can eliminate water and HF in the electrolyte and reduce the interference of water and HF on silane; and isocyanate compounds are also a high-temperature resistant elastic polymer after polymerization, which can be combined with silane containing carbon-carbon unsaturated bonds to jointly protect the interface film constructed by FEC, ultimately improving the high-temperature performance.

[0046] When silane contains isocyanate groups, it can not only eliminate HF and water in the electrolyte, but also build a high-temperature resistant interface film to achieve the purpose of inhibiting gas production. When silane containing isocyanate groups and isocyanate compounds work together, the Si-O bond can be directly combined with the isocyanate group to form an elastic polymer with Si-O components as the skeleton, which greatly improves the mechanical strength of the interface film, effectively assists FEC in building a complete interface film, and reduces the negative effects caused by the expansion of the silicon negative electrode. In addition, silane containing isocyanate groups can effectively reduce the amount of isocyanate compounds added.

[0047] Since the synergistic effect of silane, FEC and isocyanate compounds can improve the electrochemical performance of the battery during the charge and discharge process of the battery, it can be understood that the content of silane, the content of FEC and the content of isocyanate compounds in the electrolyte will have a crucial impact on the performance of the battery. Therefore, the present invention can further select the content of silane, FEC and isocyanate compounds in the electrolyte in order to improve the comprehensive performance of the battery. Exemplarily, in some embodiments of the present invention, based on the total mass of the electrolyte, the mass percentage of silane is 0.5%-1%; and / or,

[0048] Based on the total mass of the electrolyte, the mass percentage of fluoroethylene carbonate is 5%-10%; and / or,

[0049] Based on the total mass of the electrolyte, the mass percentage of the isocyanate compound is 0.1%-0.5%.

[0050] In some embodiments of the present invention, the electrolyte further comprises a lithium salt, and the mass percentage of the lithium salt is 12.5%-18% based on the total mass of the electrolyte.

[0051] In the present invention, when the content of lithium salt is within the above range, lithium ions in the lithium salt can preferentially participate in the construction of the interface film, and anions in the lithium salt can also participate in the construction of the interface film. Excessive lithium salt will enrich the interface film with lithium-containing compounds during the process of constructing the interface film, thereby reducing the interface impedance of the interface film and improving the low-temperature performance of the battery; and the excess lithium salt also has a self-sacrificing effect, reducing the loss of active lithium in the positive electrode active material of the battery, thereby improving the initial efficiency of the battery.

[0052] Furthermore, based on the total mass of the electrolyte, the total mass percentage of the lithium salt may be 14%-18%.

[0053] The present invention does not particularly limit the lithium salt, which can be a lithium salt commonly used in the art. Exemplarily, the lithium salt can be selected from at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium tetrafluoroborate, lithium bisoxalate borate, lithium difluorooxalate phosphate and lithium tetrafluorooxalate phosphate. In some embodiments, when the lithium salt is a mixed lithium salt including lithium hexafluorophosphate, lithium bisfluorosulfonyl imide and lithium difluorophosphate, the cycle life and high temperature performance of the battery can be further improved. The reason is that: in the mixed lithium salt, lithium difluorophosphate can effectively reduce the impedance of the electrolyte and improve the cycle life of the battery; bisfluorosulfonyl imide lithium salt has better thermal stability and can improve the high temperature cycle performance of the battery; lithium hexafluorophosphate can passivate aluminum foil and eliminate the negative effects of bisfluorosulfonyl imide lithium salt. The synergistic effect of the three can further improve the cycle life and high temperature performance of the battery.

[0054] Furthermore, based on the total mass of the electrolyte, the mass percentage of lithium hexafluorophosphate is 6%-15%, the mass percentage of lithium bis(fluorosulfonyl)imide is 1%-6%, and the mass percentage of lithium difluorophosphate is 0.5%-1%.

[0055] It can be understood that the electrolyte of the present invention also includes a solvent, and the solvent can be an organic solvent. For example, the solvent can be selected from at least two of chain carbonates, cyclic carbonates, fluorinated cyclic carbonates, fluorinated chain carbonates, chain carboxylates, cyclic carboxylates and fluorinated chain ethers.

[0056] Further, the solvent can be selected from at least two of diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethylene carbonate, propylene carbonate, methyl trifluoroethyl carbonate, difluoroethylene carbonate, ethyl acetate, propyl propionate, γ-butyrolactone, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, and methyl nonafluorobutyl ether.

[0057] In some embodiments, when the solvent is selected from ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate and dimethyl carbonate, the comprehensive performance of the electrolyte can be further improved. In addition, based on the total mass of the electrolyte, the total amount of ethylene carbonate and propylene carbonate added can be 17.46%-23.22%, and the total amount of ethyl methyl carbonate, diethyl carbonate and dimethyl carbonate added can be 40.74%-54.18%.

[0058] The electrolyte of the present invention may also include other additives commonly used in the art. For example, it may be selected from at least one of vinyl sulfite, 1,4-butane sultone, 1,3-propylene sultone, 1,3-propane sultone, vinyl sulfate, maleic anhydride, tris(trimethylsilyl) borate, difluoroethylene carbonate, and vinylene carbonate. In some embodiments, based on the total mass of the electrolyte, the mass percentage of other additives may be 0.03%-4%. In particular, when the mass percentage of other additives is 0.5% to 3.8% based on the total mass of the electrolyte, the comprehensive performance of the electrolyte can be further improved.

[0059] A second aspect of the present invention provides a battery, comprising the above-mentioned electrolyte.

[0060] It can be understood that the battery of the present invention further includes a positive electrode sheet, a negative electrode sheet, a separator and an outer package.

[0061] The present invention does not specifically limit the positive electrode sheet, and it can be a common positive electrode sheet in the art. In some embodiments, the positive electrode active material in the positive electrode sheet can be at least one of lithium cobalt oxide, lithium iron phosphate and a ternary material. Further, the positive electrode active material can be a ternary material.

[0062] The present invention does not specifically limit the negative electrode sheet, and it can be a common negative electrode sheet in the art. In some embodiments, the negative electrode active material in the negative electrode sheet can be selected from at least one of artificial graphite, natural graphite, lithium titanate, silicon, silicon carbon, silicon oxygen, and silicon metal compound. Further, the negative electrode active material can be silicon carbon and / or silicon oxygen.

[0063] In particular, when high-nickel ternary positive electrode materials and silicon-carbon negative electrode materials are used together to prepare batteries, the advantages of 4680 batteries can be fully utilized.

[0064] In the specific application process, the electrolyte will form a stable SEI film on the surface of the negative electrode, and the electrolyte is not easy to produce gas at high temperatures. Therefore, the battery containing the electrolyte of the present invention can have excellent room temperature cycle performance, high temperature cycle performance and high temperature storage performance.

[0065] The electrolyte of the present invention and its application are described in detail below through specific embodiments.

[0066] Example 1

[0067] The battery of this embodiment is prepared by a method comprising the following steps:

[0068] (1) Preparation of positive electrode

[0069] The positive electrode active material NCM811, the binder polyvinylidene fluoride (PVDF), and the conductive agent acetylene black were mixed in a mass ratio of 96.5:2:1.5, N-methylpyrrolidone (NMP) was added, and the mixture was stirred under the action of a vacuum stirrer until the raw materials were mixed into a positive electrode slurry with uniform fluidity;

[0070] The positive electrode slurry was evenly coated on the two surfaces of 7μm thick aluminum foil, baked in an oven with 5 different temperature gradients, and then dried in an oven at 120℃ for 8h. After roller pressing, the compaction density of the positive electrode active layer was controlled to be 3.5g / cm 3 , cut to obtain the positive electrode sheet.

[0071] (2) Negative electrode preparation

[0072] The negative electrode active material carbon dioxide @ graphite (the mass percentage of silicon dioxide is 10%), the thickener sodium carboxymethyl cellulose (CMC-Na), the binder styrene butadiene rubber, the conductive agent acetylene black, and the conductive agent single-walled carbon nanotube (SWCNT) are mixed in a mass ratio of 95.9:1:2:1:0.1, deionized water is added, and a negative electrode slurry is obtained under the action of a vacuum mixer;

[0073] The negative electrode slurry was evenly coated on the two surfaces of the copper foil with a thickness of 6 μm, and then dried (temperature: 85 °C, time: 5 h) and rolled to control the compaction density of the negative electrode active layer to 1.65 g / cm 3 , die-cut to obtain the negative electrode sheet.

[0074] (3) Preparation of electrolyte

[0075] In a glove box filled with argon (water <10ppm, oxygen <1ppm), ethylene carbonate (EC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and propylene carbonate (PC) were mixed at a mass ratio of 1.5:1.5:5:2 to obtain a mixed solution. Fully dried lithium salt, FEC, organic silane compound, and isocyanate compound were quickly added to the mixed solution to obtain an electrolyte. The specific composition of the electrolyte is shown in Table 1.

[0076] (4) Preparation of lithium-ion batteries

[0077] The positive electrode sheet of step (1), the separator, and the negative electrode sheet of step (2) are stacked in sequence, and then wound to obtain a bare battery cell without liquid injection;

[0078] Placing the bare cell in an outer packaging foil, injecting the electrolyte of step (3) into the dried bare cell, and performing vacuum packaging, standing, forming, shaping, sorting and other processes to obtain the desired lithium-ion battery;

[0079] The diaphragm is a coated polyethylene diaphragm with a thickness of 8 μm.

[0080] Examples 2-43, Comparative Examples 1-7

[0081] The compositions of the electrolytes of Examples 2-43 and Comparative Examples 1-7 are substantially the same as those of Example 1, except for the differences shown in Table 1.

[0082] The electrolyte in Example 1 was replaced with the electrolytes in Examples 2-43 and Comparative Examples 1-7, respectively, to obtain lithium ion batteries of Examples 2-43 and Comparative Examples 1-7, respectively.

[0083] Table 1

[0084]

[0085]

[0086]

[0087] In Table 1, the molecular formula of C is as follows;

[0088]

[0089] Performance Testing

[0090] The following performance tests were performed on the batteries in the embodiment and the comparative example, and the test results are shown in Table 2;

[0091] 1) Initial effectiveness test

[0092] The battery was charged to 4.2V at 0.1C constant current at 45℃, and the first step charging capacity was recorded as Q1. After aging at 45℃ and secondary sealing, the battery was charged to 4.2V at 0.1C constant current at room temperature 25℃, and charged to a cut-off current of 0.05C at a constant voltage of 4.2V, and the second step charging capacity was recorded as Q2. The battery was then discharged to 2.75V at 0.2C, and the first step discharge capacity was recorded as Q3. The first efficiency of the battery = Q3 / (Q1+Q2)*100%.

[0093] 2) Normal temperature cycle performance test

[0094] The battery was charged at room temperature (25°C) at a constant current of 1C to 4.2V, and at a constant voltage of 4.4V to a cut-off current of 0.05C. The battery was then discharged at 1C to 2.75V. The charge and discharge were repeated for 600 cycles. The discharge capacity of the 600th cycle was recorded and divided by the discharge capacity of the 1st cycle to obtain the capacity retention rate.

[0095] 3) High temperature cycle performance test

[0096] The battery was charged at a high temperature of 45°C at a constant current of 1C to 4.2V, and then charged at a constant voltage of 4.2V to a cut-off current of 0.05C. Then the battery was discharged at 1C to 2.75V. The charge and discharge were repeated for 200 cycles. The discharge capacity of the 200th cycle was recorded and divided by the discharge capacity of the first cycle to obtain the capacity retention rate.

[0097] 4) High temperature storage performance test

[0098] The battery was charged to 4.2V at 1C constant current at room temperature 25℃, charged to a cut-off current of 0.05C at a constant voltage of 4.2V, and then discharged at a constant current of 0.5C, and the discharge capacity was recorded as C2. At room temperature 25℃, the battery was charged to 4.2V at 1C constant current, charged to a cut-off current of 0.05C at a constant voltage of 4.42, and then the battery was transferred to a high temperature of 60℃ and left for 7 days, and then discharged at a constant current of 0.5C, and the discharge capacity was recorded as C3, and the 60℃ capacity retention rate = C3 / C2*100%.

[0099] 5) Initial DCIR test

[0100] The divided battery was charged to 4.2V at 1C at room temperature, left for 5 minutes, then discharged at 1C for 30 minutes, left for 1 hour, and then discharged at 2C for 10 seconds, and the DCIR of the battery at 50% SOC was calculated.

[0101] Table 2

[0102]

[0103]

[0104] As shown in Table 2, when the electrolyte includes specific silane, FEC and isocyanate compounds, the battery can have excellent first efficiency, room temperature cycle performance, high temperature cycle performance and high temperature storage performance, and reduce the impedance of the battery;

[0105] Furthermore, it can be seen from Examples 9 and 10, and Examples 1 and 17 that by further selecting the content of lithium salt in the electrolyte, the first efficiency, room temperature cycle performance, high temperature cycle performance and high temperature storage performance of the battery can be improved, and the impedance of the battery can be reduced;

[0106] It can be seen from Example 9 and Example 1 that by making a specific selection of the type of lithium salt, the first efficiency, room temperature cycle performance, high temperature cycle performance and high temperature storage performance of the battery can be improved, and the impedance of the battery can be reduced;

[0107] It can be seen from Examples 1 and 3 that when the silane contains Si-O bonds, the obtained electrolyte can significantly improve the normal temperature cycle performance, high temperature cycle performance and high temperature storage performance of the battery when applied to the battery;

[0108] It can be seen from Examples 2 and 3 that when the silane is a symmetrical structure, the obtained electrolyte can significantly improve the first efficiency, room temperature cycle performance, high temperature cycle performance and high temperature storage performance of the battery when applied to the battery, and reduce the impedance of the battery;

[0109] It can be seen from Example 1 and Example 6 that by further selecting the content of FEC in the electrolyte, the high-temperature cycle performance and high-temperature storage performance of the battery can be significantly improved without affecting the initial efficiency, room-temperature cycle performance and impedance of the battery.

[0110] It can be seen from Example 1 and Example 7 that the overall performance of the battery can be significantly improved by specifically selecting the content of silane in the electrolyte;

[0111] It can be seen from Example 1 and Example 8 that the comprehensive performance of the battery can be significantly improved by specifically selecting the content of the isocyanate compound in the electrolyte;

[0112] It can be seen from Example 13 and Example 11, Example 12, and Examples 14-17 and Examples 1-5 that the comprehensive performance of the battery can be significantly improved by making specific selections of isocyanate compounds.

[0113] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An electrolyte, characterized in that: Comprising silane, isocyanate compounds and fluoroethylene carbonate; based on the total mass of the electrolyte, the mass percentage of the silane is 0.6-1%, the mass percentage of the fluoroethylene carbonate is 6-10%, and the mass percentage of the isocyanate compound is 0.1-0.5%; The silane is selected from the compounds shown in the following structures; 2. The electrolyte according to claim 1, characterized in that The electrolyte further comprises lithium salt, and based on the total mass of the electrolyte, the mass percentage of the lithium salt is 12.5%-18%.

3. A battery, characterized in that: Comprising the electrolyte described in claim 1 or 2.

Citation Information

Patent Citations

  • High-voltage lithium ion battery non-aqueous electrolyte and lithium ion battery containing electrolyte

    CN111129595A

  • High-nickel lithium ion battery electrolyte used under high voltage and lithium ion battery

    CN112563572A

  • Lithium ion battery electrolyte and lithium ion battery

    CN113451651A

  • Lithium battery electrolyte and lithium battery

    CN114039090A

  • Electrolyte, secondary battery and electric equipment

    CN115911560A